Development and Validation of a Game-Based Assessment for Complex Problem Solving - Jian Li; Yi Ming Li; Yun-Xuan Xing; Bo Zhang; Yun Tang; Fritz Drasgow (Journal of Intelligence)
Complex problem solving (CPS) refers to a set of higher-order capacities that allow an individual to interact with a dynamic environment and solve complex problems. The purpose of this study was to develop and validate Sokoban, a game-based assessment of the planning–execution stage of the CPS framework proposed by PISA 2012. The psychometric properties of this instrument were examined in a large sample of Chinese students (n = 1145) ranging from elementary to tertiary education. The results supported the two-faceted nature of Sokoban, as well as providing preliminary evidence about criterion-related and predictive validity for the planning–execution stages of complex problem solving. These empirical results lend support to the validity of this game-based assessment, as well as its practical implications in educational settings.